Quantificação de bactérias nitrificantes, desnitrificantes e heterotróficas em reator de leito estruturado utilizado no tratamento de efluentes de laticínios - Macieirinha, Victória Romualdo (2017)
The effluent from the dairy industries as result to the concentration of organic matter and nitrogen must receive treatment before being released to the water bodies, thus minimizing the contamination of their waters. In biological treatment systems, heterotrophic bacteria remove organic matter and part of the nitrogen. Oxidizing bacteria ammonia, oxidizing bacteria nitrite and denitrifying bacteria (heterotrophic) are responsible for the transformation of ammoniacal nitrogen into more oxidized forms (nitrification) and subsequent release of gaseous nitrogen (denitrification). Thus, the objective of this work was to estimate the concentration of nitrifying, denitrifying and heterotrophic bacteria in a structured bed reactor treating dairy effluent, submitted to two operational conditions, Phase I with continuous aeration and Phase II with intermittent aeration. For this study, a structured bed reactor with a useful volume of 2.125 L with polyurethane foam support material (MS) was used. Two operational phases were evaluated: Phase I (continuous aeration) and Phase II (intermittent aeration - 2 h of aeration (AE) / 1h without aeration (AN), with Hydraulic Holding Time (TDH) of 16 hours. Samples of MS, effluent (EF) and sludge (LD) were collected at different reactor operating times to determination the concentration of BOA, BON and denitrifiers using the Most Probable Number (MPN) technique and heterotrophic bacteria using the standard counting technique in plates. The results of the quantification of the bacteria were compared to the chemical parameters of pH, total alkalinity, DQOT, Nitrogen Kjeldhl Total (NKT), N-ammoniacal-N-NH4 +, nitrite- N-NO2- and nitrate- N-NO3-. Comparing the microbiological data, in Phase I, due to the operational condition of the system being constantly supplying oxygen, the nitrification process was favored, but the denitrification process, which occurs in the absence of oxygen, was disadvantaged by this phase. In phase II, the system was operating with intermittent aeration, allowing the simultaneous nitrification and denitrification process, which is confirmed by the better nitrogen removal efficiency of the system (76%). In Phase II it is possible to observe that there was an increase in the amount of UFC / mL of the heterotrophic bacteria indicating that this group can be better adapted to the operating conditions, besides showing greater abundance and diversity of heterotrophic bacteria in the Petri dishes analyzed. Based on the results, it is possible to conclude that the reactor was efficient in the removal of nitrogen and organic matter due to the bacteria present in the reactor.